KOMUNITAS SEBAGAI UNSUR PENTING BAGI PENGEMBANGAN KEWIRAUSAHAAN: SEBUAH PEMBELAJARAN DARI PERTANIAN HORTIKULTURA DI JAWA BARAT - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Yosini Deliana (Universitas Galuh Ciamis, 2021)
Entrepreneurship occurs in a space with heterogeneous actors, where there are complex relationships between these actors. This research focuses on understanding entrepreneurship and agricultural communities in the context of economic development. Entrepreneurship research is felt to have not paid enough attention to understanding the community as a group of actors who influence the entrepreneurial behavior of an entrepreneur). We believe that entrepreneurship is greatly influenced by the existence of a community consisting of various stakeholders (government, universities and the private sector). An understanding of the entrepreneurial phenomenon can be obtained by understanding individual interactions with existing opportunities and the environment in which the entrepreneur operates. The relationship between farmers as entrepreneurs and the community as a place where farmers cultivate is important. Social capital, values, norms and culture contained in the community can influence entrepreneurship, both positively and vice versa. Likewise, entrepreneurial activities contribute to the life of society as a whole. Community and entrepreneurship are two entities that influence each other, each of which cannot stand alone. The next challenge for us as entrepreneurship researchers is to expand the scope of research to understand entrepreneurship more comprehensively from various points of view.